COMPUTATIONAL MODELLING OF CELLULOSE AND CARBON-BASED NANOWIRES USING FIRST PRINCIPLES DENSITY FUNCTIONAL THEORY - Alvanh Alem G. Pido; Art Anthony Z. Munio (International Engineering Journal For Research & Development, 2022)
Nanomaterials play very important role in nanotechnology. Conducting investigations about their properties and applications require standard computational models that mimic their physical aspects. In this, paper, we designed a nanowire model of cellulose and carbon-based nanomaterials (H-doped CNT) with the aid of first-principles Density Functional Theory. All the structures were optimized until the convergence criterion of 10-08 au is reached. We made sure that the ionic forces between atoms are small enough in accordance with the Hellman-Feynman Theorem. For the cellulose, only two polymerizations with 12 C atoms, 20 H atoms and 10 O atoms are considered, forming a cellulose unit. We have seen that its structure is formed via beta-glycosidic bonds. For the carbon-based nanomaterial, we generated a pristine (9,9) carbon nanotube (CNT) and introduced substitutional H doping, making it an H-doped CNT. All the structures where then meshed, forming nanowires. This paper is designed for future researchers about the modelling of nanostructures.